Ekonomi dan Ekologi: Dampak terhadap Pembangunan Ekowisata - Dadi Dadi (IPM2KPE, 2022)
This study aimed to discuss and further analyze the role of economy and ecology on ecotourism development in the Ciamis Regency area. This research method is descriptive. The results showed that tourism objects around the tourist sites, namely Karangkamulyan tourism, Cukang taneuh, and several tourist villages, still have diversity so that they become the main attraction for visitors who have come there. and at the same time making Ciamis Regency one of the barometers of cultural and natural tourism centers that are still maintained today in Indonesia. By utilizing the support of the village community there, the ecotourism program that has been promoted by the local government can run properly and be able to improve the welfare and livelihoods of the people of Ciamis Regency as a whole. In addition, the local government has also improved the system of promoting the tourism agenda in Ciamis Regency to be more dynamic, creative, and full of positive messages, so that the number of tourist arrivals visiting several tourist destinations has always increased quite rapidly. In conclusion, the real condition of all tourism objects in Ciamis Regency is indeed very unique for tourists, through a collaboration that has been properly structured, Ciamis Regency has fulfilled several indicators in building tourism objects that emphasize the preservation of nature and indigenous culture. Keywords: Ecology, Economy, Tourism development